Міф і символ як відображення духовного становлення культурної свідомості - Гудзенко-Александрук, Олена Георгіївна; Hudzenko-Aleksandruk, Olena H. (Волинський державний університет імені Лесі Українки, 2006)
У статті відзначається, що міф і символ можуть розглядатися як відображення духовного становлення культурної свідомості. Це засвідчує повторюваність міфологічних сюжетів від століття до століття, від культури до культури, архетипічність міфологічних постатей та існування фундаментальних символів. За всіма цими явищами, на думку автора, проглядається зв’язок із пошуками відповідей на одвічне світоглядне питання про мету людського життя. In the article it is stated that the myth and the symbol can be viewed as the reflection of the spiritual development of the cultural consciousness. It is proved by the repetition of the mythological subjects from one century to another, from one culture to another, by the architype of the mythological figures and the existance of the fundamental symbols. Through all this phenomena, according to the point of view of the author, the connection with the search for the answer on the eternal question about the aim of the human life is seen.
Myth and Symbol as the Reflection of the Spiritual Development of the Cultural Consciousness
Keywords: міф; символ; духовне становлення; культурна свідомість; архетип; myth; symbol; spiritual development; cultural consciousness; architype